Disponibilidad, consumo y utilización biológica de alimentos en Bolivia: Análisis y perspectivas (1990-2030) - Blanca Rivero Lobo; Francisco Javier Aliaga (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2015)
– This paper evaluates four dimensions of food security (ie availability, sovereignty, stability and consumption and biological utilization). Finding gaps for food groups: fruits and vegetables, proteins and carbohydrates, from comparing the supply of each product with minimum nutritional requirements of the Bolivian population in the period 1990 to 2012. The most important result of the research is that food group, only the carbohydrate group meets the dimensions studied. Both groups of proteins, such as fruits and vegetables do not meet any dimension. Is also evidence that there are cultural factors that materially affect the feed. Likewise, there are no incentives or policies on food security in the long term, so that a position of vulnerability is generated. These nutritional gaps are indicators of malnutrition and food shortages.
Keywords: Q11; Q18; Y40; 330; Food Security and Nutrition; Food Insecurity; Food Security and Food Sovereignty